Sexual Survey: A Cross-cultural Perspective - Cardoso, Fernando Luiz (Psicologia: Teoria e Pesquisa, 2012)
This is a comparative cross-cultural investigation and an analysis of the sexual life of presumably middle class college students of four countries: Israel, Colombia, Canada and Brazil. Post graduation-level students of the Institute for Advanced Studies in Human Sexuality (IASHS) in San Francisco collected the data as a PhD requirement. The data analysis revealed that, even though members of various sample groups speak different languages and belong to distinct cultures, they exhibit some similar aspects in their sexual life. Additionally, comparisons were made with the data of the NHSLS Report (USA) in a few selected topics and, again, more similarities were found among the international university students.